Use of imaging techniques to identify efficient controlled release systems of Lactobacillus rhamnosus GG during in vitro digestion. Issue 4 (13th March 2017) - Guerin, Justine; Burgain, Jennifer; Borges, Frédéric; Bhandari, Bhesh; Desobry, Stéphane; Scher, Joël; Gaiani, Claire
Abstract : Complementary microscopy techniques were used to highlight the importance of matrix formulation on lactic acid bacteria delivery system efficiency. Abstract : Matrix composition plays a crucial role in the controlled release of viable and functional bacteria in the intestine. Imaging tools such as electronic and confocal microscopies were used in this work to investigate the influence of matrix composition on matrix integrity and porosity, bacterial spatial distribution and viability during simulated in vitro digestion. L. rhamnosus GG was encapsulated in matrices having different casein/whey protein ratios. The formulation with a casein/whey ratio of 60/40 presented a porous weak gel structure that resulted in its fast disintegration in gastric media showing the presence of dead bacteria in the intestine. For the formulation with a casein/whey ratio of 100/0, the matrix was dense with a strong gel structure. At the end of the intestine, total disintegration of microparticles was not achieved and bacteria were still embedded in the matrix instead of being liberated. Only the intermediate formulation (casein/whey-80/20) permitted a good bacterial protection in the stomach and release of viable bacteria during intestinal digestion.